Chemical Composition and α-Glucosidase Inhibitory Activity of Vietnamese Citrus Peels Essential Oils. (26th September 2016) - Dang, Nguyen Hai; Nhung, Pham Huong; Mai Anh, Bui Thi; Thu Thuy, Dinh Thi; Minh, Chau Van; Dat, Nguyen Tien
Abstract : Background . Inhibition of α -glucosidase is an important factor to control postprandial hyperglycemia in type 2 diabetes mellitus. Citrus essential oils (CEO) are among the most widely used essential oils, and some of them exhibited promising antidiabetic effect. However, the α -glucosidase inhibition of CEO has not been investigated so far. The present work aims to evaluate the α -glucosidase inhibition of essential oils from six Vietnamese Citrus peels. Methods . The chemical composition of essential oils obtained by hydrodistillation from six Citrus peels was analyzed by GC-MS. All essential oils were tested for their inhibitory activity on α -glucosidase using p -nitrophenyl- α -D-glucopyranoside as substrate. Results . In Buddha's hand and lime peels, the major components were limonene (59.0–61.31%) and γ -terpinene (13.98–23.84%) while limonene (90.95–95.74%) was most abundant in pomelo, orange, tangerine, and calamondin peels. Among the essential oils, the Buddha's hand oil showed the most significant α -glucosidase inhibitory effect with the IC50 value of 412.2  μ g/mL. The combination of the Buddha's hand essential oil and the antidiabetic drug acarbose increased the inhibitory effect. Conclusions . The results suggested the potential use of Buddha's hand essential oil as an alternative in treatment of type 2 diabetes mellitus.